Navigating Challenges In Larger ESL Classrooms: Effective Strategies For Teaching Diverse Student Abilities - Abdul Ghafoor , Aqila Hafeez , Mehmood Ul Hassan , Afshan Gul Shahzadi , Lubna Shahzadi , Muhammad Usman Safdar Butt , Rabia Tariq (Migration Letters, 2024)
This study explores the challenges faced by ESL (English as a Second Language) teachers in managing mixed-ability classes within larger classroom settings at Riphah International University, Faisalabad. The research investigates various issues encountered by teachers, including difficulties in material selection, lesson planning, classroom management, and providing individualized feedback. Data was gathered through interviews with 10 ESL teachers, revealing common concerns such as diverse student abilities, linguistic backgrounds, and motiva[1]tional levels. Strategies employed by teachers to address these challenges include the eclectic approach, direct method, and communicative language teaching, tailored to meet the diverse needs of students. The study underscores the importance of teacher preparedness, positive attitudes, and ongoing professional development in enhancing teaching effectiveness. Limitations include the study’s focus on a specific department and a small sample size, suggesting avenues for future research to broaden the scope and depth of understanding in ESL teaching practices. Research utilized semi-structured interviews and Braun and Clark’s (2006) thematic analysis for data interpretation via NVIVO. Findings underscored the high frequency of challenges in teaching mixed ability classes, emphasizing the need for effective solutions. Effective class management and appropriate selection of materials emerged as crucial strategies, with student-centered approaches proving most successful.